Emotion suppression in multiple social contexts and its effects on psychosocial functioning: An investigation with Chinese samples. Issue 4 (3rd October 2016) - Zhou, Ting; Shang, Zhe; Wang, Dengfeng
Abstract : The present study examines the psychosocial consequences of emotion suppression and the moderating effect of social context in the link between emotion suppression and psychosocial functioning with two samples of Chinese undergraduate students. Suppression of happiness and sadness in five social contexts (with family members, close friends, classmates, teachers and strangers) and psychosocial functioning were investigated. The results indicate that the general level of happiness suppression negatively predicted individuals' psychosocial functioning, while sadness suppression was positively associated with psychosocial functioning. The moderating effect of social context was significant in the association between happiness suppression and psychosocial functioning, while its moderating effect was not significant for sadness. Moreover, the context differentiation (CD) of happiness suppression positively predicted psychosocial functioning, while the effect of CD of sadness suppression was not significant. The results of the present study extend the existing literature by suggesting the importance of taking social context and the specific type of emotion into account when examining the psychosocial adaptation of emotion suppression. New findings were also added to understand the effects of emotion suppression on psychosocial functioning for Chinese people. In the Chinese cultural context, which emphasizes regulating one's behaviours based on situational requirements, low levels of happiness suppression and high levels of sadness suppression appeared to be a psychosocially adaptive emotional display pattern.